The Brexit and Gibraltar: The last thread of the British exit? - Varga, Tímea (POLARITIES, 2023)
The United Kingdom has officially left the European Union on 31 December, 2020. How-ever, the procedure that has begun with the Brexit referendum in 2016 is still not complete: there are certain questions to be answered and deals to be made. One of the biggest problems is the question of the so-called hard borders: Northern Ireland and Gi-braltar. Even though the UK and Spain could finally agree on a deal in the end of December 2020 which could make Gibraltar part of the Schengen Area, the problem is yet to be solved. A transition period has started on the 1 January 2021, in the end of which a treaty will have to be signed by both countries, agreeing on the status of the peninsula, however, that has not happened so far. In this paper I am addressing the difficult situation of the peninsula, what this new deal could mean for London, Madrid and Gibraltar. Furthermore, I would also like to elaborate on prospects for the future treaty, and whether Brexit could change the fact that the peninsula belongs to the United Kingdom.